2014
DOI: 10.4317/medoral.19167
|View full text |Cite
|
Sign up to set email alerts
|

Effect of posterior gingival smile on the perception of smile esthetics

Abstract: Objectives: To evaluate and compare the influence of posterior gummy smile on the perception of smile esthetics by orthodontists, general-dentists and laypersons. Study Design: A frontal photograph of a smile with normal gum exposure was chosen and manipulated digitally using Adobe Photoshop C3 to generate three further images with posterior gum exposure of 4, 6 and 8mm. These four images were assessed by the three evaluator groups: orthodontists (n=40), general-dentists (n=40) and laypersons (n=40). Both ort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
2
9
0
Order By: Relevance
“…A few studies have focused on the influence of posterior gingival display on smile attractiveness, with results similar to the present study . Rodriguez‐Martinez et al demonstrated that excessive posterior gingival display compromised smile attractiveness. Crawford et al reported a correlation between position of the posterior gingival margin and smile esthetics.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…A few studies have focused on the influence of posterior gingival display on smile attractiveness, with results similar to the present study . Rodriguez‐Martinez et al demonstrated that excessive posterior gingival display compromised smile attractiveness. Crawford et al reported a correlation between position of the posterior gingival margin and smile esthetics.…”
Section: Discussionsupporting
confidence: 87%
“…Another previous study, however, reported a contradictory finding of no correlation between anterior gingival display and smile esthetics . A few studies have focused on the influence of posterior gingival display on smile attractiveness, with results similar to the present study . Rodriguez‐Martinez et al demonstrated that excessive posterior gingival display compromised smile attractiveness.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Significant differences were found among the four teeth group (14,15,24,25) and the median value for all teeth tested was 1.32 mm. When comparing the FPM with SPM according to distance of GZ to ZL, there was statistically difference between groups (P < 0.001), and SPM exhibited higher values than FPM.…”
Section: Resultsmentioning
confidence: 88%
“…[14] In addition to this, posterior gummy smile plays an important part in perceived smile esthetics. [15] Aesthetic considerations in smile design have focused mainly on the anterior teeth region and in parallel to this, Chu et al concluded that the GZL in an AC direction of lateral incisors relative to the gingival tangential zenith line joining adjacent CI and canine was approximately 1 mm under healthy conditions [9] and Hochman et al [3] concluded that the importance of maxillary anterior dental papillae display during dynamic smiling should not be left undiagnosed. However, many subjects may display PMs or even first and second molars as well [16] and in parallel to this, Kapagiannidis et al [12] evaluated frequency of tooth and gingival display in the PM region.…”
Section: Discussionmentioning
confidence: 99%